2007
DOI: 10.1002/ange.200604844
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Formation by Highly CO2‐Soluble Bisureas Containing Peracetylated Carbohydrate Groups

Abstract: Supercritical carbon dioxide (scCO 2 ) has attracted interest as an environmentally benign solvent, [1] but its practical usage is limited by the low CO 2 -solubility of polar and high-molecularweight compounds. To enhance the CO 2 -solubility of such compounds, CO 2 -philic surfactants, [2,3] dispersants, [4,5] thickeners, [6] and polymers [5,7] have been designed. Early success was achieved by the use of polyfluoroalkyl groups: various derivatives incorporating these groups showed enhanced CO 2 -solubility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…[22] In a marked improvement to synthetic efficiency, Enick, Hamilton, and co-workers showed that protection and deprotection can be circumvented by performing the reaction under acidic conditions. [23] In the presence of AcOH, the nucleophilicity of the amine is attenuated, thereby allowing the acylation of all five hydroxy groups of d-glucamine (14) to occur in one step, thus affording 15 in 72 % yield (Scheme 7).…”
Section: Proton-mediated Chemoselectivitymentioning
confidence: 99%
“…[22] In a marked improvement to synthetic efficiency, Enick, Hamilton, and co-workers showed that protection and deprotection can be circumvented by performing the reaction under acidic conditions. [23] In the presence of AcOH, the nucleophilicity of the amine is attenuated, thereby allowing the acylation of all five hydroxy groups of d-glucamine (14) to occur in one step, thus affording 15 in 72 % yield (Scheme 7).…”
Section: Proton-mediated Chemoselectivitymentioning
confidence: 99%
“…The reactions of aminopolyols 1-3 with isocyanates 4-6 gave rise to a series of asymmetrically substituted monoureas (11)(12)(13)(14)(15)(16)(17)(18)(19) with different structural variations of the headand tail-group moieties (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…[11] This study, however, focuses on more amphiphilic substances, paying attention to unprotected derivatives at the sugar moiety and assessing the propensity for self-organization and aggregation in the search for more biodegradable materials. Such results are comprehensively shown in this article and complement current studies by other groups.…”
Section: Introductionmentioning
confidence: 99%
“…Die Synthesen polyacetylierter Zucker wie D ‐Glucamin ( 15 ) sind daher meist langwierig und beruhen auf mehrstufigen Sequenzen von Schützung/Entschützung 22. Eine signifikante Verbesserung erbrachte hier ein Ansatz von Enick und Hamilton, die zeigen konnten, dass sich Schützung und Entschützung unter sauren Reaktionsbedingungen vermeiden lassen 23. Im speziellen Fall wurde in Gegenwart von AcOH die Nucleophilie des Amins abgeschwächt, und die Acylierung aller fünf Hydroxygruppen von D ‐Glucamin ( 14 ) zur Bildung von 15 gelang in einem Schritt mit einer Ausbeute von 72 % (Schema ).…”
Section: Chemoselektive Umwandlungen Mit Beteiligung Gesättigter Kunclassified